The British Imperial Preference System - Glickman, David L. (Quarterly Journal of Economics, 1947)
Relation to the proposed International Trade Organization, 439. — I. Background of the Ottawa Conference, 440. — The Ottawa agreements, 443. — Effects on Empire trade, 446. — II. Effects of Imperial Preference on the United States: United Kingdom, 451; Canada, 458; Australia, 461; New Zealand, 463; South Africa, 466; India, 467. — III. Conclusions, 468.